Competitive adsorption behavior of hydrocarbon(s)/CO2 mixtures in a double-nanopore system using molecular simulations. (15th September 2019) - Liu, Yueliang; Ma, Xiaomin; Li, Huazhou Andy; Hou, Jian
Graphical abstract: Abstract: CO2 injection into shale reservoirs has been recently proposed as a promising method that can be used to enhance hydrocarbon recovery from shale reservoirs. Adsorption behavior of hydrocarbon(s)/CO2 mixtures under shale-reservoir conditions plays an important role in affecting the efficiency of CO2 -enhanced hydrocarbon recovery from shale. In organic pores residing in shale reservoirs, the adsorption behavior of hydrocarbon(s)/CO2 mixtures can be significantly affected by the strong fluid/pore-wall interactions. In this work, a double-nanopore system comprising of two pores with sizes of 1 nm and 3 nm is built; then the competitive adsorption behavior of hydrocarbon(s)/CO2 mixtures (i.e., C1 / n C4, C1 /CO2, n C4 /CO2, and C1 / n C4 /CO2 mixtures) is investigated in this double-nanopore system using the molecular dynamic (MD) simulations. Firstly, the competitive adsorption behavior of C1 / n C4 mixture in double-nanopore system is studied with a depressurization manner. The effects of pressure and pore size distribution on competitive adsorption between hydrocarbons and CO2 are discussed. To investigate the efficiency of CO2 in replacing C1 or n C4 molecules from organic pores, dynamic distribution characteristics of C1 /CO2, n C4 /CO2, and C1 / n C4 /CO2 mixtures in the double-nanopore system are further investigated. The competitive adsorption behavior of C1 / n C4 mixture indicates that, in both nanopores, as pressure decreases, adsorption of lighter hydrocarbon (i.e., C1 ) decreases significantly, but adsorption of heavier component (i.e., n C4 ) increases slightly. It suggests that as pressure decreases, the lighter hydrocarbons can be easily extracted from nanopores, while the heavier hydrocarbons may not be readily produced. Adsorption behavior of C1 /CO2 indicates that CO2 can help the C1 recovery from nanopores; meanwhile, the recovery efficiency in the larger pore, (i.e., 3 nm), is much higher than that in the smaller pore (i.e., 1 nm). On the contrary, as pressure decreases, adsorption of n C4 in n C4 /CO2 mixtures in both nanopores is becoming stronger with the presence of CO2 ; the same behavior is also observed for C1 / n C4 /CO2 mixture. This implies that, although CO2 injection may help the recovery of lighter hydrocarbons (e.g., C1 ), but may not be an efficient agent for the recovery of heavier hydrocarbons (e.g., n C4 ).